PERBANDINGAN TEKNIK MARMET DAN PIJAT OKSITOSIN TERHADAP PRODUKSI ASI PADA IBU POSTPARTUM - Ega Harisa Hanggreini; Misrawati " "; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   The purpose of this research was to identify comparative of marmet technique and oxytocin massage  on maternal postpartum milk production using quasy eksperiment with pre test and post test design with two comparison treatment design. Sample of this study were 34 people which divided into 17 people as marmet technique and 17 people as a oxytocin massage group based on inclusion criteria using purposive sampling technique. Each group got intervensions for 30 minutes each day. This research measured by observation sheet. The univariate analysis was conducted to show frequency distribution and bivariat analysis was conducted by dependent sample T- test and Independent sample T- test. The statistic showed p value (0,003) < α (0,05) which means that there was differences between comparative marmet technique and oxytocin massage on maternal postpartum milk production. The result shows that mean of milk production after being given marmet technique was more high with value 18,500 compared with oxytocin massage with value 17,735. Which means marmet technique more effective in increase milk production on maternal postpartum compared than oxytocin massage with 0,765 difference. This research is recommended marmet technique to be applied as nursing intervention to increase milk production in maternal postpartum. Keyword: Oxytocin massage, milk production, marmet technique